Perbedaan Pola Pikir Karyawan Generasi X dan Generasi Y (Milenial) dalam Pemanfaatan Teknologi Informasi terhadap Peningkatkan Efektivitas Kerja: Studi Kasus: Universitas Langlangbuana Bandung - Devi Febrianti; Inne Satyawisudarini; Dedi Junaedi (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Information technology is a crucial instrument for enhancing work effectiveness in the digital era, yet the potential mindset differences between generations are often perceived to influence technology adoption and individual performance. This study aims to analyze the influence of IT-related mindset on work effectiveness and compare work effectiveness between Generation X and Generation Y employees at Universitas Langlangbuana. The study employed a quantitative method using a census sampling technique with 83 respondents. Data analysis was conducted using multiple linear regression and Independent Samples T-Test via IBM SPSS 27 software. The results indicate that neither Generation X’s nor Generation Y’s mindset significantly influences work effectiveness. Furthermore, there were no significant differences found in IT-utilization mindset or work effectiveness between the two generations. These findings suggest that within Universitas Langlangbuana, generation is not a primary differentiator for work effectiveness. Both generations demonstrated similar response profiles, likely due to their adaptation to the same prevailing work ecosystem, implying that other factors, such as individual work experience or organizational culture, may be more dominant in determining employees' work effectiveness.